The Relationship between Hybrid Learning Infrastructure and Learning Effectiveness at UIN Sunan Gunung Djati Bandung - Ismatul Kholilah; Hary Priatna Sanusi; Ambar Sri Lestari (Kelola: Jurnal Manajemen Pendidikan, 2025)
Hybrid learning has emerged as an innovative approach in higher education, integrating online and face-to-face instruction to enhance academic flexibility. However, its effectiveness largely depends on the availability and readiness of educational infrastructure, including digital resources and learning support facilities. This study investigates the relationship between hybrid learning infrastructure and learning effectiveness in higher education, employing a quantitative survey method with a cross-sectional design. A total of 100 students were selected as respondents through stratified random sampling. Data were collected using a likert-scale questionnaire and analyzed through Pearson correlation analysis. The findings reveal a significant positive relationship between hybrid learning infrastructure and learning effectiveness, with hybrid learning laboratories identified as the most influential factor. However, synchronous learning encounters technical challenges that hinder its effectiveness. These results highlight the critical role of robust digital infrastructure in enhancing learning effectiveness. Therefore, strategic investment in digital facilities and the optimization of instructional design are essential for the sustainable transformation of higher education.